On Mother Midwifery Care Ruling With Moringa Leaves Utilization Production To Accelerate BPM Linda Asi In Asmita, Amd.Keb Pekanbaru: On Mother Midwifery Care Ruling With Moringa Leaves Utilization Production To Accelerate BPM Linda Asi In Asmita, Amd.Keb Pekanbaru - Octa Dwienda Ristica (Institute Of Computer Science (IOCS), 2020)
Puerperal period starts after the placenta is born and ends when the tool contents back as a previous state. At postnatal breastfeeding baby breastfeeding exclusively with no specified time limit. Factors affecting milk production is less rest and nutritional status of mothers are not fulfilled, the effort to do yaitumengkonsusmsi Moringa leaf vegetable nodes and breastfeeding indefinitely in tentukan.Tujuan care to examine the use of Moringa leaf vegetable nodes to facilitate milk production in weeks The first postnatal on Ny.D P1A0H1 in BPM Linda Asmita, Amd. Keb in Pekanbaru, the test results using Moringa leaf vegetable nodes with 100 g giving a significant impact on both the mother's milk is based on the quality of breast milk. The method in this care with a case study approach, the research subject is Ny. D P1A0H1 age of 25 years, the results of care delivery Moringa leaf vegetable nodes to facilitate milk production Ny.D be smoother and increased by 50% from 70 ml before consuming Moringa leaf vegetable nodes. After midwifery care in Ny. D for 1 minngu milk production to be smooth. Hopefully this care can be made in reference to facilitate the production of breast milk in the first week post partum and health workers can improve the guidance, especially in postpartum mothers primigravida